A Strategy to Control the Reactivation of Frustrated Lewis Pairs from Shelf‐Stable Carbene Borane Complexes. (28th August 2015) - Hoshimoto, Yoichi; Kinoshita, Takuya; Ohashi, Masato; Ogoshi, Sensuke
Abstract N‐Phosphine oxide substituted imidazolylidenes (PoxIms) have been synthesized and fully characterized. These species can undergo significant changes to the spatial environment surrounding their carbene center through rotation of the phosphine oxide moiety. Either classical Lewis adducts (CLAs) or frustrated Lewis pairs (FLPs) are thus formed with B(C6F5)3 depending on the orientation of the phosphine oxide group. A strategy to reactivate FLPs from CLAs by exploiting molecular motions that are responsive to external stimuli has therefore been developed. The reactivation conditions were successfully controlled by tuning the strain in the PoxIm–B(C6F5)3 complexes so that reactivation only occurred above ambient temperature.